Змішані кристали ZnSxSe1–x як можливі матеріали для детекторів альфа та рентгенівського випромінювання - Trubaieva, O. G.; Chaika, M. A.; Zelenskaya, O. V. (Publishing house "Academperiodika", 2018)
A possibility to use ZnSxSe1−x as a material for the detection of X-rays and alpha particles has been studied. The influence of the sulfur content on the properties of bulk ZnSxSe1−x crystals is analyzed. Six specimens with different component contents were grown, by using the Bridgman–Stockbarger method: ZnS0.07Se0.93, ZnS0.15Se0.85, ZnS0.22Se0.78, ZnS0.28Se0.72, ZnS0.32Se0.68, and ZnS0.39Se0.61. The intensity of X-ray luminescence spectra of ZnSxSe1−x crystals is found to increase with the sulfur content and reaches a maximum for the composition ZnS0.22Se0.78. The luminescence light yield of mixed ZnSxSe1−x crystals is higher than that of commercial ZnSe(Te) and ZnSe(Al) crystals. The advantages of mixed crystals based onZnSxSe1−x over the ZnS(Te) and ZnSe(Al) crystals have been discussed.